Dinamika Pendidikan Islam pada Masa Daulah Umayyah dan Peranannya dalam Pengembangan Pendidikan Islam - Wilda Apriliani; Muhammad Zalnur; Fauza Masyhudi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The Umayyad period marked an important phase in the history of Islamic education, where there were significant developments in educational institutions, curricula, and the teaching of various religious and worldly sciences. The discussion about the Umayyad dynasty uses the method used is library research, namely by collecting data by understanding and studying theories from various literature. The results of educational policy during the Umayyad Daulah era were heavily influenced by political interests, which caused education to be concentrated among the elite. However, there were also positive developments, such as the formation of early madrasas and the widespread teaching of Islamic sciences, such as the Koran, hadith, fiqh, and Arabic language sciences. Caliphs and scholars played an important role in spreading education and establishing intellectual traditions that would later influence Islam's subsequent glory days, such as under the Abbasid Daula. Islamic education during the Umayyad period played a strategic role in the development of knowledge and the spread of Islamic teachings, even though it was colored by political and social dynamics.